Evaluation of an alternative treatment protocol by aglepristone to induce parturition in ewes with an experimental model of early pregnancy toxemia - Ozalp, G. R.; Yavuz, A.; Seker, I.; Udum-Kucuksen, D.; Risvanli, A.; Korlu, Y. (Elsevier Science Inc, 2018)
A new protocol with aglepristone to induce parturition in ewes with pregnancy toxemia has been reported in the present manuscript. Four experimental groups were defined: Group AG5 (n = 10), Group DEX (n = 10), Group NC (n = 5) and Group PT (n = 5) in which ewes were injected twice with 10 mg/kg of aglepristone and 5 ml dexamethasone in first two groups, respectively; whereas negative control and pregnancy toxemia groups received no treatment for parturition induction. Different clinical parameters associated with parturition in ewes and their newborns were investigated. Blood hematology and biochemical measurements were carried out both in ewes and lambs. Blood pH values of lambs were recorded during the study. The injection time-lambing time, injection time-vaginal discharge intervals, placental expulsion periods, placental weight and vaginal delivery interval between lambs, hematological and biochemical results were not statistically different among the groups (p > 0,05). Increased NEFA and 3-HBA concentrations accompanied the disease and all ewes in AG, DEX and PT Groups developed clinical pregnancy toxemia (NEFA; P = 0,009) and beta-HBA; (P = 0,039). The differences in rectal body temperature of lambs were not significant (p > 0,05), whereas birth weight was found statistically significant among groups (p <0,05). Blood pH, biochemical and hematologic measurements of lambs had also significant differences depending on different time points. Parturition pathology by means of incomplete cervical dilatation was severely observed in DEX Group. The results of this study show that aglepristone application in pregnancy toxemia to induce parturition could precisely control lambing time without any side effects in either mothers or lambs. Apart from these, it could be speculated that dexamethasone seems to induce parturition causing crucial pathologies, which results in important and risky changes in newborns' life. Incomplete cervical dilatation and continued ineffective uterine contractions could be a major factor of newborn losses because of placental separation and cessation of blood supply. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Ewe; Parturition induction; Pregnancy toxemia; Aglepristone; Dexamethasone